2021
DOI: 10.3389/fimmu.2021.662866
|View full text |Cite
|
Sign up to set email alerts
|

Of Lymph Nodes and CLL Cells: Deciphering the Role of CCR7 in the Pathogenesis of CLL and Understanding Its Potential as Therapeutic Target

Abstract: The lymph node (LN) is an essential tissue for achieving effective immune responses but it is also critical in the pathogenesis of chronic lymphocytic leukemia (CLL). Within the multitude of signaling pathways aberrantly regulated in CLL the homeostatic axis composed by the chemokine receptor CCR7 and its ligands is the main driver for directing immune cells to home into the LN. In this literature review, we address the roles of CCR7 in the pathophysiology of CLL, and how this chemokine receptor is of critical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 230 publications
(453 reference statements)
0
15
0
Order By: Relevance
“…Indeed, pioneering pre-clinical studies using CCR7 function-blocking single-chain antibodies demonstrated that these pre-clinical biologicals blocked T-ALL cell transmigration across a human brain endothelial cell monolayer, and Ca 2+ mobilization in vitro [ 308 ]. More recently, an anti-CCR7 antibody was used to reduce CLL migration to the lymph nodes and the anticipated clinical trials will further examine the efficacy/safety of this anti-CCR7 therapy [ 309 ]. Moreover, systemic anti-CCR7 therapy might be warranted if the benefits outweigh the risks of compromising normal immune responses, which will depend on the length of therapy to some extent.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, pioneering pre-clinical studies using CCR7 function-blocking single-chain antibodies demonstrated that these pre-clinical biologicals blocked T-ALL cell transmigration across a human brain endothelial cell monolayer, and Ca 2+ mobilization in vitro [ 308 ]. More recently, an anti-CCR7 antibody was used to reduce CLL migration to the lymph nodes and the anticipated clinical trials will further examine the efficacy/safety of this anti-CCR7 therapy [ 309 ]. Moreover, systemic anti-CCR7 therapy might be warranted if the benefits outweigh the risks of compromising normal immune responses, which will depend on the length of therapy to some extent.…”
Section: Discussionmentioning
confidence: 99%
“…While CLL B-cells overexpress CCR7 [ 28 ], T-cells from treatment-naïve patients have comparable expression as healthy counterparts [ 29 , 30 , 31 ]. We and others have previously shown ibrutinib to cause a clear reduction of surface CCR7 levels in CLL B-cells that may eventually affect trafficking of malignant cells into the LN [ 22 , 32 , 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…Whereas most blood circulating T cells express CCR7, peripheral DCs induce this chemokine receptor only upon encounter of danger signals ( 13 , 14 , 26 ). CCR7 induction has been shown to predominantly involve the transcription factors NF-κB and AP-1 ( 47 , 48 ). Interestingly, among all chemokine receptors, CCR7 possesses a unique signal sequence that facilitates its package into COPII vesicles for efficient ER to Golgi trafficking, and thus surface expression ( 36 ).…”
Section: Discussionmentioning
confidence: 99%